Development of Student Worksheets (LKPD) Based on Problem Based Learning (PBL) in Mathematics Learning for Grade IV Students of Elementary School - Rastinah Rastinah; Elya Rosalina; Sari Pertiwi (CV. Edujavare Publishing, 2026)
In general, education can be interpreted as an activity to learn the knowledge, abilities, and habits of a group of people that are passed down from one generation to the next through teaching, practice, and research methods. This study aims to determine the validity, practicality, and effectiveness of the Development of Student Worksheets (LKPD) Based on Problem Based Learning (PBL) in Mathematics Learning for Fourth Grade Students of SD Negeri 2 Sukamana. Data collection techniques used were observation, interviews, and documentation. Data analysis techniques in the study were analyzed descriptively qualitatively. This study is a Research and Development (R&D) study using a 4-D development model, which consists of the stages of defining, designing, developing, and disseminating. The subjects of this study were 26 fourth grade students of SD Negeri 2 Sukamana. Data were collected using a validation questionnaire, a practicality questionnaire, and learning outcome tests in the form of pre-tests and post-tests. The results showed that the developed LKPD had a high level of validity, with a score of 0.92 from language experts, 0.86 from media experts, and 0.94 from material experts with an overall average of 0.90 which is included in the